Safety evaluation of secretome proteins from paenibacillus polymyxa kp10 and lactococcus lactis gh1 as the potential antimicrobial therapeutic agent - Zainal Baharin, Nurul Hana; Khairil Mokhtar, Nur Fadhilah; Mohd Desa, Mohd Nasir; Dzaraly, Nurul Diana; Muthanna, Abdulrahman; Mohd Hashim, Amalia; Lani, Mohd Nizam; Mustafa, Shuhaimi (IIUM Press, 2023)
The secretome proteins of Paenibacillus polymyxa Kp10 and Lactococcus lactis Gh1 were previously found to have the potential for controlling the antibiotic-resistant pathogen. Therefore, their safety evaluation to ensure consumer health is deemed important. This study was to evaluate the toxicity effect of both secretome proteins in human cells against Medical Research Council cell strain 5 (MRC5). Then, their antibacterial activities were tested in human serum to assess the stability of both secretome proteins. The results showed no cytotoxic effects of either secretome protein when MRC5 cells were treated up to the determined concentrations. Therefore, no IC50 was determined. In addition, human serum did not affect the antibacterial activity of both secretome proteins against Methicillin-resistant Staphylococcus aureus (MRSA) and Vancomycin-resistant Enterococcus (VRE). In conclusion, both secretome proteins are potentially safe for future development as a potential therapeutic agent.